Per un lessico della propaganda barocca: il Kitsch (ENTHYMEMA, 2019)
This paper focuses on baroque propaganda, and it justifies the anachronism of such category by bringing its heuristic potential to light. Through the analysis of some well-known models (Michel Foucault’s raison d’état, Pierre Bourdieu’s symbolic capital, Jürgen Habermas’s open sphere), the paper points out the main features of consensus building in 17th-century Europe: intermediality, productivity, asystematicity. Aiming at compiling a lexicon of baroque propaganda, the paper also focuses on the concept of Kitsch. The inquiry primarily concerns the painted cycle of Peter Paul Rubens at the Luxembourg palace and the poem Adone by Giovan Battista Marino. The goal is to define the role played by ancient mythology in the representation of Ancien Régime political power.